2020
DOI: 10.1080/10409238.2020.1841726
|View full text |Cite
|
Sign up to set email alerts
|

Repeat RNA expansion disorders of the nervous system: post-transcriptional mechanisms and therapeutic strategies

Abstract: Dozens of incurable neurological disorders result from expansion of short repeat sequences in both coding and non-coding regions of the transcriptome. Short repeat expansions underlie microsatellite repeat expansion (MRE) disorders including myotonic dystrophy (DM1, CUG 50–3,500 in DMPK ; DM2, CCTG 75–11,000 in ZNF9), fragile X tremor ataxia syndrome (FXTAS, CGG 50–200 in FMR1), spinal bulbar muscular atrophy (SBMA, CAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 159 publications
(256 reference statements)
0
25
0
Order By: Relevance
“…As aforementioned, microsatellite repeat expansion (MRE) in both coding and non-coding regions of the genome has been associated with many neurological disorders, such as Huntington’s disease (HD), spinocerebellar ataxia, Friedreich ataxia, myotonic dystrophy, frontotemporal dementia (FTD), and amyotrophic lateral sclerosis (ALS) [ 161 ]. The hallmark for these MRE-associated disorders is the disturbances in the RNA metabolism resulting from the expansion of the repeat sequence which affects the proper translation and protein degradation [ 162 ].…”
Section: Rna Therapies To Treat Single-gene Neurological Disordersmentioning
confidence: 99%
“…As aforementioned, microsatellite repeat expansion (MRE) in both coding and non-coding regions of the genome has been associated with many neurological disorders, such as Huntington’s disease (HD), spinocerebellar ataxia, Friedreich ataxia, myotonic dystrophy, frontotemporal dementia (FTD), and amyotrophic lateral sclerosis (ALS) [ 161 ]. The hallmark for these MRE-associated disorders is the disturbances in the RNA metabolism resulting from the expansion of the repeat sequence which affects the proper translation and protein degradation [ 162 ].…”
Section: Rna Therapies To Treat Single-gene Neurological Disordersmentioning
confidence: 99%
“…Large trinucleotide (CGG) expansion (i.e., full mutations, FM) in the 5’ UTR of the FMR1 gene are associated with the neurodevelopmental disorder Fragile X Syndrome (FXS) while smaller, premutations (PM) are associated with Fragile X-associated tremor and ataxia syndrome (FXTAS), a late onset condition characterized by executive functioning decline and progressive cerebellar ataxia, presenting in 40-70% of PM carriers (Fu et al, 1991; Pieretti et al, 1991; Verkerk et al, 1991; Jacquemont et al, 2003; Grigsby et al, 2016). In the latter, neuropathological and imaging studies have identified intranuclear neuronal and astrocytic inclusions, prominent white matter abnormalities including myelin pallor and spongiosis, and characteristic T2 white matter hyperintensities on MRI (Jacquemont et al, 2003; Tassone et al, 2004; Cohen et al, 2006; Greco et al, 2006; Schwartz et al, 2021). In contrast, in Fragile X syndrome, an early-onset neurodevelopmental disorder characterized by intellectual disability, autistic symptoms and characteristic facial features (Martin & Bell, 1943; Turner et al, 1975), only subtle functional changes in white matter in humans have been identified on imaging (Hallahan et al, 2011; Sandoval et al, 2018; Swanson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies in post-mortem human brain in both FXS and FXTAS have focused on bulk cellular analysis, which does not resolve cell-type specific molecular alterations. Whereas it is possible that the cellular heterogeneity of the human CNS may mask toxic levels of FMR1 mRNA, other hypotheses, including an inappropriate DNA damage response, mitochondrial stress, and polyglycine-containing peptide accumulation, have been put forth as alternative hypotheses to explain the pathophysiology of FXTAS (Garcia-Arocena & Hagerman, 2010;Sellier et al, 2017;Schwartz et al, 2021). It is also possible that reduced FMRP contributes to PM pathology in a developmentally distinct manner from the total loss that occurs in FXS.…”
mentioning
confidence: 99%
“…Neurodegenerative disorders devastate millions of lives worldwide and impose an increasing socio-economic burden (Kalia and Lang, 2015 ; Feigin et al, 2017 ; Erkkinen et al, 2018 ; El-Hayek et al, 2019 ). Research within the last decades has helped to clarify the mechanisms underlying each disease and suggested new therapeutic approaches (Fu et al, 2018 ; Ga et al, 2018 ; Jucker and Walker, 2018 ; Reich et al, 2018 ; Lassmann, 2019 ; Savelieff et al, 2019 ; Schwartz et al, 2021 ). A decisive step is the identification of molecular culprits that provoke or contribute to the dysfunction and degeneration of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Huntingtin has been at the center of attention as the long-sought gene bearing Huntington’s disease (HD)-causing mutations (The Huntington’s Disease Collaborative Research Group, 1993 ). Repeat expansions similar to those induced by the Huntingtin alleles cause neurodegeneration in numerous diseases including ALS and frontotemporal dementia by combinations of distinct molecular mechanisms (Malik et al, 2021 ; Schwartz et al, 2021 ). Research on multiple sclerosis (MS) has focused on immune and glial cells since chronic inflammation and demyelination are known pathologic changes preceding neurodegeneration (Faissner et al, 2019 ; Lassmann, 2019 ; Voet et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%